(untitled) (Jurnal Teknologi Industri Pertanian, 2024)
A technopreneur’s social network is a key factor in the early stages of the entrepreneurial process which includes the stages of searching for ideas, acquiring resources, and gaining legitimacy for the development of his business. It is hoped that a technopreneur’s ability to create, manage and maintain social networks can improve the performance of the business he starts. This research aimed to map the social network of technopreneurs in the early stages of their entrepreneurial process and analyze their evolution in the three initial stages. The technopreneur social networks studied were betweenness, centrality, density and diversity. Networks are built using an ego network approach. The egos used were eight new businesses that are members of a business incubator with the criteria of food and non-food agro-industry, business unit age 2 – 5 years, in wall which means having an office in the incubator and out wall which means having an office outside the incubator. The network was analyzed using software. The results of the analysis show that technopreneurs who are on the in wall have a denser network than those on the out wall due to the large number of actors who come from the incubator network. The parameter values of betweenness, centrality, diversity and density change at each stage of the entrepreneurial process. Technopreneurs need diversity and betweenness in the idea search phase to increase the flow of information and ideas. Technopreneurs need centrality and density in the resource acquisition phase to increase resource access. Centrality and density are needed in the legitimacy phase to increase a technopreneur’s reputation. Keywords: agroindustry, entrepreneurial stages, social networking, technopreneur